2009
DOI: 10.1103/physrevlett.102.126805
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Noise in Electrically Biased Bilayer Graphene

Abstract: We demonstrate that the low-frequency resistance fluctuations, or noise, in bilayer graphene are strongly connected to its band structure and display a minimum when the gap between the conduction and valence band is zero. Using double-gated bilayer graphene devices we have tuned the zero gap and charge neutrality points independently, which offers a versatile mechanism to investigate the low-energy band structure, charge localization, and screening properties of bilayer graphene.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
111
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(122 citation statements)
references
References 23 publications
9
111
2
Order By: Relevance
“…The charging and discharging of these charge traps modulate the electro-chemical potential more strongly than the gate, hence making the noise level insensitive to the gate voltage. 8,19 The noise power measured in our devices is down to f à S I =I 2 b ¼ 6:2  10 À10 (for the sample S3 having an area of 3.7 lm 2 ), which is so far the lowest value ever reported for graphene based devices of similar size. 2,20 This could well be anticipated for suspended bilayer graphene samples, where the contact resistance fluctuations due to charged traps can be better screened than in monolayer graphene.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The charging and discharging of these charge traps modulate the electro-chemical potential more strongly than the gate, hence making the noise level insensitive to the gate voltage. 8,19 The noise power measured in our devices is down to f à S I =I 2 b ¼ 6:2  10 À10 (for the sample S3 having an area of 3.7 lm 2 ), which is so far the lowest value ever reported for graphene based devices of similar size. 2,20 This could well be anticipated for suspended bilayer graphene samples, where the contact resistance fluctuations due to charged traps can be better screened than in monolayer graphene.…”
mentioning
confidence: 97%
“…6 This reduced noise in bilayer graphene devices is due to its unique band structure and charge distribution between the two layers. 8 Our experiment is motivated by Zhang et al 7 and Lin and Avouris. 6 We have studied the low frequency noise in suspended bilayer graphene devices and found lower 1/f noise level in our devices in comparison to similar suspended carbon devices.…”
mentioning
confidence: 99%
“…The noise level in graphene FETs is strongly affected by the quality of the graphene-metal contacts and environmental exposure [15]. Several reports suggested that the low-frequency noise can be reduced in bilayer graphene (BLG) devices as compared to that in the single-layer graphene (SLG) devices [11,14]. The physical mechanism for the reduction and the dominant noise sources, e.g.…”
mentioning
confidence: 99%
“…The low-frequency noise in graphene field-effect transistors (FETs) has the drain-current noise spectral density S I~1 /f for the frequency f below 100 kHz [11][12][13][14][15][16][17][18]. Some graphene devices also exhibit the generation-recombination (G-R) noise bulges with the time constants =1/(2f o ) of ~0.3 -1.1 s (f o is the corner frequency) [12].…”
mentioning
confidence: 99%
“…Flicker noise in graphene arises from the fluctuation in the number of charge carriers and their mobility. Techniques to reduce it such as electron irradiation [28][29][30][31][32] can be explored in this context. In addition, the high NEP in graphene is also due to the low sensitivity arising in part because of the weak dependence of the graphene resistance with temperature.…”
mentioning
confidence: 99%